Pelatihan Rintisan Sanggar Jurnalistik Dakwah Guna Meningkatkan Literasi Digital Remaja Di Desa Pladen Kabupaten Kudus - Iftah Lana Maula; Verry Budi Hartanto; Ahmad Jumanto; Eko Darmanto (Muria Jurnal Layanan Masyarakat, 2022)
At this time there are many teenagers in Pladen Village, Kudus Regency whose daily life cannot be separated from their gadgets. They look for news on the internet, sometimes the authenticity of which is unclear, causing the youth in Pladen Village to have a literacy crisis. In implementing this program, the team uses 6 stages, the first is pre-preparation. The second is preparation. The third is Execution. Fifth is Evaluation. The sixth is a sustainable program. The purpose of this program is to improve the literacy and knowledge skills of teenagers in Pladen Village, Jekulo Subdistrict, Kudus Regency to avoid hoax news that will be made in journalistic applications and benefit the surrounding environment. With this program, it is hoped that the public will get information distribution media, can be used as promotional media and can be a trusted source in distinguishing hoax news.